Relationship between Aortic pulse wave velocity and left ventricular mass in a group of African ancestry is not accounted for by Aortic pressures - Bello, Hamza (My University, 2017)
Aortic pulse wave velocity (PWV) and backward waves, as determined from wave separation analysis, predict cardiovascular events beyond brachial blood pressure (BP). However, the extent to which these aortic hemodynamic variables contribute independent of each other is uncertain. In 749 randomly selected participants of African ancestry we therefore assessed the extent to which relationships between aortic PWV or backward wave pressures (Pb)(and hence central aortic pulse pressure [PPc]) and left ventricular mass index (LVMI) occur independent of each other. Aortic PWV, PPc, forward wave pressure (Pf) and Pb were determined using radial applanation tonometry and SphygmoCor software and LVMI using echocardiography. 44.5% of participants had an increased LVMI-ht1.7. With adjustments for age, brachial systolic BP or PP and additional confounders, PPc and Pb, but not Pf was independently related to LVMI and LV hypertrophy (LVH) in both men and women. However, PWV was independently associated with LVMI in women (partial r=0.16, p<0.001), but not in men (partial r=0.03) and PWV was independently associated with LVH in women (p<0.05), but not in men (p=0.07). With PWV and Pb included in the same multivariate regression models, PWV (partial r=0.14, p<0.005) and Pb (partial r=0.10, p<0.05) contributed to a similar extent to variations in LVMI in women. In addition, with PWV and Pb included in the same multivariate regression models, PWV (p<0.05) and Pb (p<0.02) contributed to LVH in women. In conclusion, aortic PWV and backward wave pressure (and hence pulse pressure) although both associated with LVMI and LVH, produce effects which are independent of each other.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, for the degree of Master of Science in Medicine. Johannesburg, 2017.
Keywords: Left Ventricular Mass Index; Pulse Wave Analysis (Pulse Wave Velocity); Arterial Pressure (Aortic Pressures)